PERKEMBANGAN DAN DAMPAK FINANCIAL TECHNOLOGY (FINTECH) TERHADAP PERILAKU MANAJEMEN KEUANGAN DI UMKM SEMARANG - Ulfah, Rahmawati; Dewi, Nur Fitri; Udriyah, Udriyah (Jaksya: Jurnal Akuntansi Syariah, 2025)
This study examines the development of fintech and its impact on financial management behavior in Micro, Small, and Medium Enterprises (MSMEs) in Semarang. Fintech, encompassing technologies such as digital payments, peer-to-peer (P2P) lending, financial management, crowdfunding, and digital insurance, has provided more inclusive and efficient access to financial services for MSMEs. Findings from various literatures indicate that fintech can enhance the operational efficiency of MSMEs through more accurate transaction recording, better financial planning, and more effective cash flow management. In Semarang, MSMEs have begun adopting fintech, although challenges such as limited digital infrastructure and low technological literacy still affect its effectiveness. This review also highlights the importance of policies that support fintech development and digital literacy education for MSMEs. This study contributes to the existing literature by integrating findings on the impact of fintech on MSMEs and identifying research gaps that require further exploration, such as the influence of local factors on technology adoption and risk mitigation strategies that can be applied. Future research recommendations include a deeper exploration of how fintech can be optimized to support the growth and resilience of MSMEs, particularly in local contexts like Semarang.